Některé problémy měření regionálních rozdílů ekonomické výkonnosti - Ježdík, Václav (Univerzita Pardubice, 2000)
The article is oriented to the appreciation of analytical methods for the regional comparison and of the measurement of the regional differences. As the principal indicarors of economic development are concidered regional gross domestic product and unemployment rate.
Keywords: Regionální politika; ekonomická úroveň; rozdíly; hodnocení; výkonnost